Preslaughter Anesthesia with Lippia alba Essential Oil Delays the Spoilage of Chilled Rhamdia quelen. Issue 2 (7th February 2018) - Veit, Juliana C.; Piccolo, Jaqueline; Scherer, Aline F.; Machado, Isadora S.; Maurer, Luana H.; Conte, Lisiane; Baldisserotto, Bernardo; Koakoski, Gessi; Menezes, Charlene C.; Loro, Vania L.; Barcellos, Leonardo J. G.; Heinzmann, Berta M.; et al.
ABSTRACT: This study evaluated whether anesthesia with essential oil (EO) of Lippia alba (300 mg L −1 for 4 min) prior to electronarcosis (128 V m −1  × 300 Hz for 5 s) or hypothermia (ice/water slurry) could delay fish spoilage during chilled storage of whole fish. Silver catfish ( Rhamdia quelen ) were subjected to two different pre-stunning treatments (water or anesthesia with EO of L. alba ) followed by two different stunning procedures (hypothermia or electrical stunning), yielding four groups ( n  = 32/group): water (control) + hypothermia, water (control) + electrical stunning, EO of L. alba  + hypothermia, and EO of L. alba  + electrical stunning. After stunning, fish were slaughtered by percussion and stored in ice. Preslaughter anesthesia with the EO of L. alba extended fish shelf life by delaying the loss of freshness (nucleotide degradation), growth of Enterobacteriaceae, and fish deterioration (sensory evaluation). Such preservative effect was most remarkable for fish that were subsequently submitted to electrical stunning, as they had the lowest demerit scores and greatest shelf life in the sensory evaluation. Our results showed that preslaughter anesthesia with EO of L. alba followed by electrical stunning can delay the loss of freshness and extend fish shelf life during chilled storage.